Anterior corpus callosotomy in multistep invasive monitoring and surgery for atonic seizures()() - Truong, Van Tri (Epilepsy Behav Case Rep, 2014)
Identifying the epileptogenic zone (EZ) in patients with refractory nonlesional frontal lobe epilepsy is frequently challenging. Intracranial EEG (icEEG) recordings are often required to better delineate the EZ, but the presence of an extensive network of connections allowing rapid ictal spread may result in bilateral homologous regional (or extremely diffuse) electrical ictal patterns. Here, we report a case where callosotomy performed after a first nonlateralizing icEEG study allowed for adequate identification of the EZ. The patient, an 18-year-old left-handed woman with daily atonic spells, had synchronous interictal and ictal epileptic activity from both supplementary motor areas (SMAs) during icEEG. Anterior partial callosotomy localized the EZ to the right SMA, as seizures were no longer associated with mirror-image ictal activity over the left SMA. Right SMA resection led to seizure freedom (follow-up of 23 months). This case exemplifies how a partial callosotomy followed by further icEEG recordings may adequately localize the EZ when initial icEEG recordings reveal bilateral synchronous focal or regional ictal activities.